QUALITY ASSESSMENT OF DIFFERENT BRANDS OF PARACETAMOL TABLETS IN YEMENI MARKET - Alsaifi, Abdulmajed; Alyahawi, Ali (Universal Journal of Pharmaceutical Research, 2018)
Objective: Paracetamol or acetaminophen is active metabolites of phenacitin. It is a widely used over-the-counter analgesic and antipyretic. Chemically, it is 4-hydroxy acetanilide (acetaminophen). Paracetamol is approved for reducing fever in people of all ages. It is commonly used for the relief of headaches, other minor aches and pains, and is a major ingredient in numerous cold and flu remedies. Many different brands and dosage forms of paracetamol are available in Yemeni market that places health practitioners in a dilemma of drug substitution in case of non-availability of a particular brand. The aim of the present study was to evaluate the quality control of four brands of paracetamol tablets (500 mg) marketed and commonly prescribed in Yemeni market. The results and findings of the present study will be interpreted and discussed. Methods: Four brands of paracetamol tablets (500 mg) were purchased from the retail pharmacy outlets and their pharmaceutical quality were assessed by using in-vitro tests according to USP and BP standards and unofficial standards as recommended by the manufacturers. The assessment of tablets included the evaluation of uniformity of weight, hardens, friability, disintegration time, dissolution test as well as assay content by UV spectrophotometric method. Results: All brands passed USP and BP standards in- vitro quality control tests prescribed for the tablets except hardens test but all products were satisfactory for hardness. Conclusion: The results indicated that the overall quality of all tested paracetamol tablets brands was satisfactory as they met the requirements of the official and unofficial quality control tests. Peer Review History: Received 22 May 2018; Revised 3 July; Accepted 28 September; Available online 15 September 2018 Academic Editor: Dr. A.A. Mgbahurike , University of Port Harcourt, Nigeria, amaka_mgbahurike@yahoo.com Reviewer(s) detail: Dr. Rashad Mohammed Musleh Alnamer , University of Thamar, Yemen, yemtiger1@yahoo.com Dr. Omid Gholami , Sabzevar University of Medical Sciences, Iran, omidghphd@gmail.com